This preview shows page 1. Sign up to view the full content.
Unformatted text preview: We have n = 3 so (1-n ) =-2. Let y = u-2 and the equation for y becomes y =-2 y + 2 . This is rst order linear and we write it as y + 2 y = 2. This I = e R (2) dt = e 2 t . Multiply by I to get ye 2 t = 2 e 2 t Integrate both sides to get ye 2 t = e 2 t + C Finally u-2 = 1 + Ce-2 t ....
View Full Document
This note was uploaded on 10/19/2011 for the course MATH 2254 taught by Professor Gilliam during the Fall '05 term at Texas Tech.
- Fall '05